High-efficiency full-range tunable on-chip power supply for ultra-low-power digital IC - Guan, Xiaofei. (2011)
With IC technology scaling into the deep sub-micron region, circuit power dissipation has become a primary concern for nowadays IC designers. Supply voltage scaling is an effective method which provides a flexible tradeoff between circuit performance and power consumption. In particular, when the circuit supply voltage is reduced to below transistor’s threshold voltage (sub-threshold operation) in a certain process technology, maximum power efficiency point can be achieved because the theoretical minimum energy operating point of most digital systems is located in the sub-threshold region. In this Final Year Project, a digitally controlled tunable on-chip power supply system has been developed with the emphases on energy-efficient along the full rage (from sub threshold to nominal supply). This report presents the whole development process of this tunable on-chip power supply system, from analysis, design to implementation and improvement. The whole supply system implemented the idea of switching DC-DC buck converter with 4 key components: UDVS Controller, PWM Signal Generator on-chip transistor buffer as well as off-chip LC low-pass filter. Efficiency Improvement has been done based on segmented transistor. Switched-Capacitor DC-DC Buck Converter, inductor-free DC-DC Buck Converter and Dead Time Optimization were analyzed as improvement methods. Functionality and Performance Testing has been done to the chip. At the end of the report, conclusions and recommendations are made for the further system development in the future.